2022
DOI: 10.21037/jtd-21-967
|View full text |Cite
|
Sign up to set email alerts
|

CT perfusion imaging can detect residual lung tumor early after radiofrequency ablation: a preliminary animal study on both tumoral and peri-tumoral region assessment

Abstract: Background: Radiofrequency ablation (RFA) is a minimally invasive procedure to treat lung cancer.Timely evaluation on residual lung tumor after RFA is crucial to the prognosis, hence, our objective is to assess CT perfusion (CTP) on detection of residual lung tumor early after RFA. Methods: CTP imaging was performed in 24 lung VX2 tumor models 1 day before and within 1 hour after RFA. CTP maps with dual-input (n=24) and single-input [n=13, with predominant ground glass opacity (GGO) after RFA] models were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The degree of tumor enhancement depends only on the amount of contrast medium in the tumor vessels. The central type of lung cancer is mainly SC, mainly supplied by bronchial artery, whereas the peripheral type of lung cancer is mainly AC with dual blood supply of bronchial artery and pulmonary artery (20,21). Because the blood supply from the bronchial artery is later than that from the pulmonary artery, the VP better reflects the blood supply of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of tumor enhancement depends only on the amount of contrast medium in the tumor vessels. The central type of lung cancer is mainly SC, mainly supplied by bronchial artery, whereas the peripheral type of lung cancer is mainly AC with dual blood supply of bronchial artery and pulmonary artery (20,21). Because the blood supply from the bronchial artery is later than that from the pulmonary artery, the VP better reflects the blood supply of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…ID reflects intravascular blood flow distribution and vascular status by quantitative analysis of iodine content, but it is influenced by many factors, including cardiac output and blood volume of the patient, concentration and flow rate of the contrast medium, and dose and rate of injection (20). NID was defined as the ratio of tumor ID to that of the aorta or subclavian arteries at the same level, and most researchers (8,(21)(22)(23) state that NID can reduce the effect of individual circulatory variability on tumor iodine content and thus more accurately reflect the blood supply of the lesion. However, in this comparison of AC and SC, we found that ID is more effective than NID in both the AP and the VP, which is consistent with the results of the study by Li et al (10).…”
Section: Discussionmentioning
confidence: 99%
“…Different diagnostic tools may be employed, alone or in association [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Computed tomography (CT) and magnetic resonance imaging (MRI) represent the traditional imaging tools employed during the pre-treatment phase in order to identify and assess the target area [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], and in surveillance of the patient to evaluate treatment efficacy and post-procedural complications [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. Ultrasound examination (US), without or with contrast medium (CEUS), is an innovative tool, utilized for problem solving during pre- and post-treatment phases [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ], although the main use of interest is the possibility of assessing immediate effects during the procedure [ 60 , 61 ].…”
Section: Imaging and Ablation Treatmentmentioning
confidence: 99%